2008
DOI: 10.1152/ajpregu.00704.2007
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of electrical propagation in the intact pregnant guinea pig uterus

Abstract: Previous studies have reported on propagation of individual spikes in isolated segments of the pregnant uterus, but there is no information on patterns of spike propagation in the intact organ. There is also no information on propagation of myometrial burst. The aim of this study was to record, at high resolution, patterns of propagation of electrical activities in the pregnant uterus. Sixteen timed-pregnant guinea pigs were euthanized at term, and their uteruses isolated. Fetuses were removed and replaced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 29 publications
8
77
3
Order By: Relevance
“…Further investigation might be dedicated to the advantages of integrating our volume conductor model with more complex descriptions of the myometrial cell AP generation [13], [14]. In view of the recent investigations on the guinea pig myometrium [12], possible limitations of the proposed model are the assumption that the myometrial tissue is isotropic and the hypothesis that APs propagate exclusively either along the longitudinal or the circumferential axis of the uterus. Therefore, in the future, the role played by the complex 3-D geometrical and anatomical structures of the myometrium in the conduction of electrical activity needs to be understood and possibly integrated in the source model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further investigation might be dedicated to the advantages of integrating our volume conductor model with more complex descriptions of the myometrial cell AP generation [13], [14]. In view of the recent investigations on the guinea pig myometrium [12], possible limitations of the proposed model are the assumption that the myometrial tissue is isotropic and the hypothesis that APs propagate exclusively either along the longitudinal or the circumferential axis of the uterus. Therefore, in the future, the role played by the complex 3-D geometrical and anatomical structures of the myometrium in the conduction of electrical activity needs to be understood and possibly integrated in the source model.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies demonstrated that the analysis of the EHG signal may play a key role for accurate monitoring of the uterine contractions, prediction of labor, and improvement of perinatal outcome [7]- [11]. However, many issues related to the conduction pattern of electrical activation are still unsolved [12].…”
Section: Modeling and Identification Of The Electrohysterographic Volmentioning
confidence: 99%
See 2 more Smart Citations
“…Each burst correspond to a single mechanical contraction of the uterus. Most of the previous literature focused on the analysis of the entire burst and only few Chiara Rabotti and Massimo Mischi are with the Department of Electrical Engineering, Eindhoven University of technology, the Netherlands C.Rabotti@tue.nl studies were dedicated to the analysis of single surface APs [3], [4], [5], i.e., single spikes extracted from the EHG. However, in-vitro studies have demonstrated that individual surface APs propagate for longer distance and with higher conduction velocity (CV) at parturition than at preterm [3].…”
Section: Introductionmentioning
confidence: 99%